The Effect of Gene Polymorphisms (ENOS G894T, PON1 and Catalase-262C?T) on Fertility and Sperm Parameters in Turkish Men with Clinical Varicocele: A Pilot Study - Ceylan, Cavil; Ceylan, Gulay G.; Artas, Hakan; Aglamus, Erdogan; Ates, Can; Yuce, Huseyin (Kuwait Medical Assoc, 2012)
Objective: Scrotal varicocele is found to be associated with increased spermatozoal reactive oxygen species (ROS) production and decreased seminal plasma antioxidant activity. Our objective was to search for an association between male infertility and gene polymorphisms (PON1, ENOS G894T and Catalase -262C -> T). Design: Controlled prospective study Setting: Ataturk and Yuksek Ihtisas Education and Training Hospitals, Ankara, Turkey Subjects: Forty primary infertile men and forty healthy men were included in the study. Patients with clinical varicocele in the study group had no endocrinopathy, no surgery for varicocele / inguinal hernia, and / or no leukospermia. They were non-smokers. Intervention: Doppler ultrasonography (USG) was performed for the patients. For genetic analysis, 5 ml of venous blood was drawn into tubes containing EDTA from each patient. Main Outcome Measures: Gene polymorphism, progressive sperm motion and vein diameter Results: Existence of gene polymorphisms was statistically important in patients who had clinical varicocele with affected progressive forward motion. We determined statistically significant rate of gene polymorphisms in enzymatic antioxidant defence systems in patients with clinical varicocele, with a diameter of spermatic vein above 2.2 mm and forward progressive sperm motion below 32% (p < 0.001). Conclusions: These polymorphisms might represent risk factors for Turkish men with clinical varicocele and forward progressive sperm motion defect. This is a pilot study. We intend to continue these studies with larger sample sizes to confirm these findings.
Keywords: gene polymorphism; male infertility; oxidative stress; varicocele